You’ve Over the Line! Muslim Consumers are Resistant to Opposite Brand Values - Firdan Thoriq Faza; Yan Putra Timur; Sulistya Rusgianto; Lu'liyatul Mutmainah (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
The consumer's antagonistic behavior towards brands is hotly discussed because of the political issues it carries. However, factors affecting Muslim consumers to reject a product still requires more paucity of empirical evidence. The current study casts the light on antecedent factors that influence Muslim consumers to reject a product, and on a pattern between the reasons for refusal and the intention to boycott a brand. The online survey was able to reach 450 respondents from the Muslim community. This paper uses scenarios from confirmed cases of Muslim consumer boycotts against Unilever brands in Indonesia. Using the snowball-sampling technique, many of the respondents were from the educated young urban Muslim community. The model was tested using partial least squares-structural equation modeling (PLS-SEM). Moreover, the interaction moderation technique was applied to examine the effect of moderators on the structural model. The results showed that brand hate fully mediates all variables except symbolic incongruity. The results further revealed that brand hate is a construct with three first-order formative triggers (religious animosity, ideological incompatibility, and subjective norms). In addition, this study theoretically contributes to providing clear delineation that brand hate is a dichotomous concept consisting of the dimensions of intention to boycott (intention to incite, intention to avoid, and intention to punish).